Financial Capacity and Output Fluctuations in an Economy with Multi-Period Financial Relationships - Gertler, Mark (Review of Economic Studies, 1992)
This paper motivates a financial propagation mechanism in the context of an intertemporal production economy with asymmetric information, and with borrowers and lenders who enter multi-period financial relationships. A key feature is that aggregate output and borrowers' "financial capacity" —the maximum overhang of past debt they may feasibly carry—are determined jointly, much in the spirit of Gurley and Shaw (1955). Expectations of future economic conditions govern financial capacity which in turn may constrain current production, especially in bad times. A small but persistent shift in aggregate conditions may have a large impact on financial capacity, making the framework capable of motivating large endogenous fluctuations in financial constraints.